A combined DFT and AIMD study: The effect of nitrogen on Tobermorite9 Å. (December 2022) - Liu, Xiaotong; Liang, Tianshui; Zhong, Wei; He, Jiujiu
Abstract: Through the ab initio molecular dynamics (AIMD) and density functional theory (DFT) calculation, the research on the N atom and N2 molecule on the Tobermorite9 Å (0 0 1) surface is conducted. The findings demonstrate that the most constant adsorption position for the N2 molecule is the top location of the Ca5 atom. Electrons are (a) lost by the Ca atom and (b) gained by the N atom, according to the charge density difference results. Then, outcomes from the partial density of states highlight that the formation of an especially weak Ca-N bond resulted from the imperceptible orbital hybridization between the N-p and Ca-d orbitals. Among the upper atoms, the deformation of the calcium atom in the Z direction is the largest, and the value is 0.02341 Å. At 1473 K, the AIMD results show that the N2 gradually develops from adsorption to desorption on the surface. The adsorption of N2 molecule on the surface is a physical adsorption. Nitrogen produces elastic deformation on hydrated calcium silicate. These findings provide profound views in understanding the N2 on hydrated calcium silicate. Graphical Abstract: ga1 Highlights: The most constant adsorption position is the top location of the Ca5 atom. Electrons are lost by the Ca atom and gained by the N atom. The PDOS highlight that the formation of an especially weak Ca-N bond. Nitrogen produces elastic deformation on hydrated calcium silicate. N2 develops from adsorption to desorption on the surface at AIMD simulation.